Causes of Maternal Mortality Based on The Three-Delays Model: A Retrospective Observational Study - Dafroyati, Yuliana; R.H Kristina, R.H Kristina; Widyastuti, Ririn; Israfil , Israfil (Green Publisher Indonesia, 2023)
Reducing maternal mortality is one of the targets for achieving global health Sustainable Development Goals (SDGs). The cause of maternal death is still a major problem. The breadth of the territory and the variety of demographic, economic, social, and cultural conditions of the Indonesian people are important to investigate regarding the causes of maternal death in the community. The purpose of this study was to find out the causes of maternal death in one of the districts in the province which is in the eastern part of Indonesia. a retrospective observational study was conducted on 23 cases of maternal death. Data collection has been carried out using the three-delay model approach. the majority of maternal deaths were caused by two delays, 1) being late in deciding to seek care at a health facility due to lack of awareness of complications (78.%), low-income families (74%), and the culture of visiting traditional healers to help with deliveries (57%), and 2 ) were late reaching health facilities due to cost and availability of transportation (52%), poor road conditions (43%), and travel time > 1 hour (39%). awareness of mothers and families about the dangers of perinatal complications is an important point that must be addressed early so as not to affect delays in making decisions to seek care at health facilities, which ultimately results in delays in reaching health facilities, and delays in receiving treatment from health workers.